Uncovering Hedge Fund Skill from the Portfolio Holdings They Hide - Agarwal, Vikas (Institutional Knowledge at Singapore Management University, 2013)
This paper studies the “confidential holdings” of institutional investors, especially hedge funds, where the quarter-end equity holdings are disclosed with a delay through amendments to Form 13F and are usually excluded from the standard databases. Funds managing large risky portfolios with nonconventional strategies seek confidentiality more frequently. Stocks in these holdings are disproportionately associated with information-sensitive events or share characteristics indicating greater information asymmetry. Confidential holdings exhibit superior performance up to 12 months, and tend to take longer to build. Together the evidence supports private information and the associated price impact as the dominant motives for confidentiality.